Effect of nano‐SiO2 on properties and microstructure of polymer modified cementitious materials at different temperatures. (18th October 2019) - Meng, Tao; Yu, Hongming; Lian, Songsong; Meng, Ruitan
Abstract: In this study, the effect of nano‐SiO2 on mechanical properties and microstructure of polymer modified cementitious (PMC) materials under 20 and 6°C was studied through strength test, X‐ray Diffraction Analysis, Mercury Intrusion Porosimetry, and Scanning Electron Microscopy. Results showed that the flexural and compressive strength of cement mortar was influenced seriously by polymer especially under low temperature condition. And nano‐SiO2 was contributed to enhance the flexural and compressive strength of PMC materials at early age under 20°C while the enhancement still existed at later age under 6°C. The disadvantage of polymer on the properties and microstructure of PMC materials at low temperature was modified by nano‐SiO2 due to the increase of hydration rate of cement, the decrease of the Ca(OH)2 (CH) orientation aggregation, the modification of pore structure, and the promotion of polymer film formation. This study provides a prospective method on the performance optimization of PMC materials.